Disruption of Multiple Distinctive Neural Networks Associated With Impulse Control Disorder in Parkinson's Disease - Filip, Pavel; Linhartová, Pavla; Hlavatá, Pavlína; Šumec, Rastislav; Baláž, Marek; Bareš, Martin; Kašpárek, Tomáš (Frontiers in Human Neuroscience, 2018)
The phenomenon of impulsivity in Parkinson’s disease appears as an arduous side effect of dopaminergic therapy with potentially detrimental consequences for the life of the patients. Although conceptualized as a result of non-physiologic chronic dopaminergic stimulation, recent advances speculate on combined disruption of other networks as well. In the search for neuroanatomical correlates of this multifaceted disturbance, this study employs two distinct, well-defined tasks of close association to motor inhibition and decision-making impulsivity, Go/No Go and Delay discounting. The fMRI and functional connectivity analysis in 21 Parkinson’s disease patients, including 8 patients suffering from severe impulse control disorder, and 28 healthy controls, revealed in impulsive Parkinson’s disease patients not only decreased fMRI activation in the dorsolateral prefrontal cortex and bilateral striatum, but also vast functional connectivity changes of both caudate nuclei as decreased connectivity to the superior parietal cortex and increased connectivity to the insular area, clearly beyond the commonly stated areas, which indicates that orbitofronto-striatal and mesolimbic functional disruptions are not the sole mechanisms underlying impulse control disorder in Parkinson’s disease. Ergo, our results present a refinement and synthesis of gradually developing ideas about the nature of impulsive control disorder in Parkinson’s disease – an umbrella term encompassing various behavioral deviations related to distinct neuronal networks and presumably neurotransmitter systems, which greatly exceed the previously envisioned dopaminergic pathways as the only culprit.